Thermodynamic equilibrium analysis of CO2 reforming of methane: elimination of carbon deposition and adjustment of H2/CO ratio - Cao, Pengfei; Adegbite, Stephen; Wu, Tao (Elsevier, 2017)
Dry (CO2) reforming of methane (DRM) is considered as a promising technique to produce syngas. In this study, to optimise the operating conditions for elimination of carbon deposition, thermodynamic calculations were carried out to understand the effect of various temperatures (550-1200 ̊C), pressures (0.05-5 MPa) and CH4/CO2 mole ratios (0.5-2) on the product of H2/CO ratio as well as the formation of carbon deposition. The suggested DRM operating conditions for carbon free regime are at a temperature greater than 1000 ̊C with CH4/CO2 mole ratio = 1 and pressure P = 0.1 MPa. The operating temperature of carbon free regime could be switched to lower temperature by either lowering the CH4/CO2 mole ratio or decreasing the reaction pressure. The results illustrated that the temperature range for severe carbon formation was between 546 ̊C and 703 ̊C. CH4 decomposition and CO disassociation reaction are considered as the major reactions contributing to carbon formation. The former was promoted at operating conditions of P ≤ 0.1 MPa and 550 ̊C ≤ T ≤ 1000 ̊C, while the latter was enhanced at operating conditions of P ≥ 0.1 MPa and T ≤ 700 ̊C. The syngas produced from optimised carbon free regime operating conditions, could be used to synthesis olefin, heavy hydrocarbons and oxygenated compounds. H2 /CO ratio could be adjusted by the changing CH4 /CO2 mole ratio and/or pressure to satisfy F-T process for different application. Since the latter is only effective when operating temperature is lower than 900 ̊C, the former is proposed as a more efficient method to adjust H2/CO ratio. When the operating temperature of DRM is over 700 ̊C, H2/CO ratio obtained at CH4/CO2 mole ratio of DRM ≤ 1 and P = 0.1 MPa is more preferable to be used for the synthesis of olefin, heavy hydrocarbons and oxygenated compounds. Otherwise the syngas is more suitable for producing alkane (C1 –C5).